Socio-economic determinants for the deployment of Climate-Smart One-Health innovations. A meta-analysis approach prioritizing Ghana and Benin - Sekabira, H.; Tepa-Yotto, G.; Tamò, Manuele; Djouaka, R.F.; Dalaa, Mustapha Alasan; Damba, O.T.; Yeboah, S.; Obeng, F.; Asare, R.; Abdoulaye, Tahirou; Nazziwa, L. (2023)
An ecosystem is inhabited by organisms that rely on it for their livelihoods. For an ecosystem to sustain life, its life-supporting components must be alive to be able to preserve both the ecosystem’s life-supporting components like soil, vegetation, water, etc., and the living organisms inhabiting the ecosystem like humans, birds, domestic, and wild animals, termed as the One-Health concept. This is indispensable for the sustainability of life. Several factors determine the ability of the ecosystem to provide ecosystem services and support life, more so amidst climate change. Hence, climate-smart (CS) One-Health innovations are essential to maintain the integrity of the ecosystem to be able to support life. However, factors that could effectively determine the deployment of such CS One-Health innovations are not well identified. This paper, closes the knowledge gap through a systematic review of literature for a meta-analysis of the socio-economic determinants for the successful deployment of CS One-Health innovations. Using a scoping review methodology, search engines like Google Scholar, PubMed, Scopus, and AgriEcon were explored extensively for literature on CS One-Health innovations. Search results were then screened and only articles that met the inclusion criteria were considered in this study. Subsequently, appropriate articles were identified for data extraction. Results revealed that political will, community participation, knowledge of CS One-Health practices, the willingness of parties to engage in multi-disciplinary collaborative activities, and level of investment (income/funds) were enablers for the deployment of CS One-Health innovations. On the other hand, behavior incompatibility with innovations, policy failure to restrict the use of toxic substances in agriculture, poor community knowledge of CS One-Health innovations, and language barriers between communities and innovators, hindered such deployment. Hence, multiple factors (fostering and hindering) must be addressed in a multi-disciplinary framework to ensure the successful deployment of CS One-Health innovations.